THE BEAUTY OF WEDDING CULTURE IN INDONESIA - Tiarnita Maria Sarjani Siregar; Ankey Dohar, Nazwa Inaya, Natasya Euodia, Susi Eria Agustina (Adisam Publisher, 2023)
Wedding ceremonies in Indonesia are a reflection of the country's diverse ethnic groups and religious beliefs. Indonesian weddings are known for their vibrant and colorful traditional attire, with each region having its unique style. The wedding festivities are a sight to behold, with traditional dances, music, and food organized by the groom. The wedding customs and practices vary based on the region, religion, and culture of the couple. Some of the most captivating wedding traditions in Indonesia include the siraman, a pre-wedding ritual where the couple is bathed in a mixture of flowers, herbs, and spices to cleanse and purify them before their marriage; the exchange of gifts or seserahan; and the bride's proposal in Minangkabau weddings. In Javanese weddings, the couple's families meet formally to set a date, decide on the budget, and divvy up tasks between themselves. Indonesian weddings are a unique opportunity to gain insight into various Indonesian cultures and social traditions. The wedding ceremonies in Indonesia are usually a festive, communal event, and the entire neighborhood where the married couple lives is welcome and expected to attend. The wedding ceremonies consist of three events: lamaran, tunangan, and pernikahan. The Nikah is held in a private ceremony or at the venue of the reception, and the most important people to felicitate the wedding are the Imam and two witnesses. The traditional Indonesian menu includes the staple fried rice, stir-fried noodles served with a variety of seafood options such as shrimp, fish, etc., in sweet and sour sauce.